Dataset untuk peran pustakawan data dalam meningkatkan literasi dan kapasitas pengelolaan data penelitian bagi komunitas penelitian dan profesional informasi di Indonesia - Sulaiman, Madiareni; Rosiyan, Nur Rizzal; Untari, Dwi; Rachmawat, Rulina; Trianggoro, Cahyo; Bakti, Ludya Arica; Yudhanto, Seno (BACA: Jurnal Dokumentasi dan Informasi, 2024)
This dataset provides information on the involvement of librarians in efforts to improve data management literacy for the research community. The data provided provides a real picture of the state of research data management in Indonesia because it uses a mixed research approach. Data collection methods were survey, interview, and content analysis. The selection of respondents and informants used purposive sampling techniques, and the criteria were librarians, researchers, lecturers, and students who dealt with research data daily. Various types and formats of data are available in this dataset, such as images, audio, text, video, and documents. This dataset is useful for stakeholders such as policymakers, librarians, researchers, and students who have competencies in research data management. By utilizing this dataset, stakeholders can identify the needs of data librarians, research data service schemes, and policy making.